Analysis of Qiaojia earthquake disasters in the Zhaotong area: Reasons for “small earthquakes and major disasters” - Wei Wang; Hong Chen; Lisiwen Ma; Yiting Xu; Minhao Qu (Natural Hazards Research, 2023)
In May 2020, a magnitude 5.0 earthquake occurred in Qiaojia County, Yunnan. This earthquake was characteristics of relatively common “small earthquakes and major disasters” in the Zhaotong area of northeastern Yunnan. Yunnan province is an area in China with a high incidence of moderately strong earthquakes with magnitude 5 or above. In this region, the unique geological structure background and geographical environment of the Zhaotong area make it the most severely damaged area not only in Yunnan but also in all of China. The geological structure of the Zhaotong area is complex, and the neotectonic movements are strong. Based on the disasters of 8 moderate and strong earthquakes in Zhaotong since 2000, this paper analyses the causes of the “small earthquakes and major disasters” in Zhaotong city and provides suggestions for disaster reduction and emergency response after an earthquake.